Selection of Indonesian Medicinal Plant Active Compounds as Inhibitor Candidates of Oncoproteins E6 and E7 Human Papillomavirus Type 16 by Molecular Docking - Riyanti Weni Syafitri; Azzania Fibriani; Reza Aditama (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
Cervical cancer cases caused by infection with Human Papillomavirus (HPV), especially HPV 16 (60.5% of cases) continue to increase every year with a high mortality rate. The current anti-cancer drugs were not only specifically targeting cancer cells, but healthy cells and can cause serious side effects. Therefore, it is necessary to find safer alternative therapies, e.g., using active compounds from natural products. The purpose of this study was to find the active compounds of Indonesian medicinal plants potentially as an inhibitor of oncoprotein E6 and E7 HPV 16, the main protein causing cervical cancer by in silico method. In this study, 711 active compounds from 187 medicinal plant species were selected based on molecular weight, solubility, gastrointestinal absorption index, and drug-likeness. Compounds that meet the criteria were tested for their affinity and interaction profile with E6 and E7 proteins through the molecular docking method. The results of this study showed 164 compounds that met the criteria. The molecular docking analysis showed nine of the most potent compounds as E6 inhibitors on the E6AP binding site and six compounds on the p53 binding site. Besides that, there were eleven most potent compounds as E7 inhibitors. The results of this study indicate that there are natural compounds that can inhibit E6 and E7 proteins and have further potential to be used as anti-HPV drugs. However, further research is needed to test these compounds in vitro and in vivo.